Microbiological Food Safety Standards Practiced by some Hotel Industries in Kumasi - Darko, Sophia (2017)
A Thesis submitted to the Department of Food Science and Technology, College of Science in partial fulfillment of the Requirements for the Degree of Master of Philosophy.